Bone marrow mesenchymal stem cells overexpressing GATA-4 improve cardiac function following myocardial infarction. (November 2019) - He, Ji-Gang; Li, Hong-Rong; Li, Bei-Bei; Xie, Qiao-Li; Yan, Dan; Wang, Xue-Juan
Introduction: The present study aimed to examine whether GATA-4 overexpressing bone marrow mesenchymal stem cells can improve cardiac function in a murine myocardial infarction model compared with bone marrow mesenchymal stem cells alone. Methods: A lentiviral-based transgenic system was used to generate bone mesenchymal stem cells which stably expressed GATA-4 (GATA-4-bone marrow mesenchymal stem cells). Apoptosis and the myogenic phenotype of the bone marrow mesenchymal stem cells were measured using Western blot and immunofluorescence assays co-cultured with cardiomyocytes. Cardiac function, bone marrow mesenchymal stem cell homing, cardiac cell apoptosis, and vessel number following transplantation were assessed, as well as the expression of c-Kit. Results: In GATA-4-bone marrow mesenchymal stem cells-cardiomyocyte co-cultures, expression of myocardial-specific antigens, cTnT, connexin-43, desmin, and α-actin was increased compared with bone marrow mesenchymal stem cells alone. Caspase 8 and cytochrome C expression was lower, and the apoptotic rate was significantly lower in GATA-4 bone marrow mesenchymal stem cells. Cardiac function following myocardial infarction was also increased in the GATA-4 bone marrow mesenchymal stem cell group as demonstrated by enhanced ejection fraction and left ventricular fractional shortening. Analysis of the cardiac tissue revealed that the GATA-4 bone marrow mesenchymal stem cell group had a greater number of DiR-positive cells suggestive of increased homing and/or survival. Transplantation with GATA-4-bone marrow mesenchymal stem cells significantly increased the number of blood vessels, decreased the proportion of apoptotic cells, and increased the mean number of cardiac c-kit-positive cells. Conclusion: GATA-4 overexpression in bone marrow mesenchymal stem cells exerts anti-apoptotic effects by targeting cytochrome C and Fas pathways, promotes the aggregation of bone marrow mesenchymal stem cells in cardiac tissue, facilitates angiogenesis, and effectively mobilizes c-kit-positive cells following myocardial infarction, leading to the improvement of cardiac function after MI.